Antitumor activity of extract and isolated compounds from Drechslera rostrata and Eurotium tonophilum - Fatmah A.S. Alasmary; Amani S. Awaad; Mehnaz Kamal; Saleh I. Alqasoumi; Mohamed E. Zain (Elsevier, 2018)
Total extracts of Drechslera rostrata and Eurotium tonophilum in addition of two isolated compounds from their cultures [di-2-ethylhexyl phthalate (H1) and 1,8-Dihydroxy-3-methoxy-6-methyl-anthraquinone (H2)] were tested for their antitumor activity using four human carcinoma cell lines. Antitumor activity was assessed by performing MTT assay to check the % cell viability. The % viability of HCT-116 (colon carcinoma), HeLa (cervical carcinoma), HEp-2 (larynx carcinoma) and HepG-2 (hepatocellular carcinoma) cells decreased after treatment with Drechslera rostrata and Eurotium tonophilum extracts, these effects were ranged from 059.0 ±  0.1 to 217.0  ±  0.3 µg/ml on all types of cancer cells. The best activity was recorded for Eurotium tonpholium extract (054.5 ± 0.3, 059.0 ± 0.5 and 059.0 ± 0.1 for HEp-2, Hela, and HepG-2 respectively). The isolated compounds (H1&H2) were found to be responsible about the activities because they recorded the lowest IC50 on tested cell lines with range of 9.5-20.3 μg/ml. Vinblastine sulphate was used as a reference standard and showed in vitro anticancer activity. This study demonstrated that all extracts and isolated compounds have antitumor activity against HCT-116, HeLa, HEp-2 and HepG-2 cells.